Taking stock: A meta-analysis of the effects of foreign language enjoyment - Botes, Elouise; Dewaele, Jean-Marc; Greiff, Samuel (Studies in Second Language Learning and Teaching, 2022)
Studies examining the positive emotion of foreign language enjoyment (FLE) have recently increased exponentially, as researchers are applying the tenets of positive psychology in applied linguistics. It is therefore an appropriate time to take stock of the current literature and conduct a preliminary meta-analysis. The relationships between FLE and four variables, namely, foreign language anxiety (FLA), willingness to communicate (WTC), academic achievement, and self-perceived achievement were examined. A total of k = 96 effect sizes were analyzed with an overall sample size of N = 28,166 in random-effects models with correlation coefficients. There was a moderate negative correlation between FLE and FLA. In turn, moderate positive correlations were found between FLE and WTC, FLE and academic achievement, and FLE and self-perceived achievement. These positive associations confirm the value of FLE in FL learning and further affirm the need for researchers to examine positive psychology constructs in the foreign language classroom.